Comparison of Non-Execution Auctions on Fiduciary Guarantees in Indo-nesia and Malaysia - Ummi Maskanah; Jefri Situmorang; Muhammad Reifal Adenafio; Ahmad Yusuf Nurwanda (IHSA Institute, 2025)
This study discusses the implementation of non-execution fiduciary auctions in Indonesia and Malaysia in the context of effectiveness, legal certainty, and protection of the parties. The approach used is normative-comparative jurisprudence, by analysing primary legal materials in the form of laws, court decisions, and legal documents in both countries, as well as secondary legal materials in the form of related scientific literature. The results of the study show that Indonesia, with its civil law system, considers fiduciary auctions to be public legal actions supervised by the state through administrative mechanisms and Constitutional Court Decision No. 18/PUU-XVII/2019. while Malaysia, with its common law system, implements contractual repossession and public auctions based on the Lease Purchase Act 1967 and the Draft Act on Security Rights over Movable Property. These differences reflect Indonesia's focus on substantive justice and debtor protection, while Malaysia excels in procedural efficiency and legal certainty for creditors. This study concludes that the ideal model for non-execution fiduciary auctions in Indonesia needs to integrate the efficiency of the Malaysian system with Indonesian legal protection through regulatory reform, digitisation of fiduciary registration, and strengthened supervision. This hybrid model is expected to create a balance between legal certainty, justice, and economic efficiency in national security law practice